การศึกษาความเป็นไปได้ในการลงทุนปรับปรุงระบบบำบัดน้ำเสียเพื่อนำก๊าซชีวภาพมาใช้ในกระบวนการผลิตของโรงงานผลิตยางแท่งมาตรฐาน 20 ในสังกัดการยางแห่งประเทศไทย ในอำเภอวังสามหมอ จังหวัดอุดรธานี: A Feasibility Study of Investment on Wastewater Treatment System to Produce Biogas for production line of Standard Rubber 20 Factories under the Rubber Authority of Thailand in Amphoe Wang Sam Mo, Changwat Udon Thani - ศิรินภาทรัพย์ ธนลักษมณ์; ทวีวัฒน์ ฆนัทนันท์; ทวีวัฒน์ พิษณุวัฒน์; บุญญานาม นรารัก (Journal of Applied Economics and Management Strategy, 2018)
การศึกษามีวัตถุประสงค์เพื่อ 1) สำรวจกระบวนการผลิตและระบบบำบัดน้ำเสียของโรงงานผลิตยางแท่งมาตรฐาน 20 ในสังกัดการยางแห่งประเทศไทย ในอำเภอวังสามหมอ จังหวัดอุดรธานี 2) ศึกษารูปแบบและทางเลือกด้านเทคนิคในการปรับปรุงระบบบำบัดน้ำเสียเพื่อนำก๊าซชีวภาพมาใช้ในกระบวนการผลิต 3) วิเคราะห์ความเป็นไปได้ด้านการเงิน และ 4) ทดสอบความสามารถในการรับความเปลี่ยนแปลงในการลงทุนปรับปรุงระบบบำบัดน้ำเสีย การศึกษาใช้ข้อมูลปฐมภูมิที่ได้จากการสังเกตแบบมีส่วนร่วมและจากการสัมภาษณ์เชิงลึก ส่วนข้อมูลทุติยภูมิได้จากการรวบรวมเอกสารวิชาการที่เกี่ยวข้องจากแหล่งต่างๆ รวมทั้งทางอินเตอร์เน็ต ข้อมูลที่ได้นำมาวิเคราะห์เชิงพรรณนาและเชิงปริมาณ เครื่องมือทางการเงินที่ใช้ได้แก่ มูลค่าปัจจุบันสุทธิ, ดัชนีความสามารถในการทำกำไร, อัตราผลตอบแทนภายใน, อัตราผลตอบแทนภายในที่มีการปรับค่าแล้ว และการทดสอบค่าความแปรเปลี่ยน ผลการศึกษาพบว่า 3 ขั้นตอนแรกของกระบวนการผลิตทั้งหมด 8 ขั้นตอนมีน้ำเสียเกิดขึ้น 150 ลูกบาศก์เมตรต่อการผลิตยาง 80 ตันต่อวัน น้ำเสียจำนวนนี้ถูกนำมาบำบัดด้วยบ่อเติมอากาศ 7 บ่อ เป็นการเพิ่มอ๊อกซิเจนให้น้ำเพื่อลดความสกปรก ทางเลือกใหม่เป็นบ่อหมักย่อยประยุกต์ให้น้ำเสียไหลตามแนวนอนปิดคลุมด้วยพลาสติกความหนาแน่นสูง เพื่อเก็บก๊าซชีวภาพที่ได้ 1,271 ลูกบาศก์เมตรต่อวัน ซึ่งเทียบเท่าก๊าซหุงต้ม 584 กิโลกรัมต่อวัน โดยใช้ 7 บ่อเดิมที่มีอยู่มาแปลงสภาพ ผลการศึกษาด้านการเงินที่อายุโครงการ 11 ปี และต้นทุนเงินทุนร้อยละ 5 ต่อปี พบว่ามูลค่าปัจจุบันสุทธิเท่ากับ 76,055 บาท อัตราผลตอบแทนภายในเท่ากับร้อยละ 5.06 อัตราผลตอบแทนภายในที่มีการปรับค่าแล้วเท่ากับร้อยละ 5.03 และ ดัชนีกำไรเท่ากับ 1.00 แสดงว่าโครงการมีความคุ้มค่าในการลงทุน ผลการทดสอบค่าความแปรเปลี่ยน บ่งชี้ว่าโครงการมีความเสี่ยงสูงต้องได้รับการดูแลอย่างใกล้ชิด เนื่องจากโครงการแทบไม่สามารถรับความเปลี่ยนแปลงในทางลบได้เลย This study aims to: 1) explore the production process and waste water treatment system of standard rubber 20 (STR 20) factories under the Rubber Authority of Thailand in Wang Sam Mo, Changwat Udon Thani 2) study the technical aspects of new alternatives in treating waste water and generating biogas supply 3) perform financial feasibility and 4) test the ability and flexibility in retaining against the change in investment. The study uses both primary and secondary data, obtained through an in-depth interview, participant observations, as well as concerned academic papers of various sources, namely online sources. Both types of data were used in descriptive and quantitative analysis. The financial tools used were net present value (NPV) internal rate of return (IRR) modified internal rate of return (MIRR) profitability index (PI) and switching value test (SVT). The study result revealed that the first 3 out of 8 steps of production process created 150 cubic meters of waste water per STR 20 production of 80 ton per day. This amount of waste water was treated by 7 aerated lagoons to increase oxygen according to biochemical oxygen demand. The new alternative was modified covered lagoon (MCL) digester based on horizontal flow and covered with the high density polyethylene plastic or polyvinyl chloride plastic. The MCL generated 1,271 cubic meters of biogas equivalent to 584 kilogram of liquefied petroleum gas by utilizing the same old 7 aerated lagoons. The financial result based on the project life of 11 years with capital cost of 5 percent shows that NPV was 76,055 baht, IRR was 5.06 percent, MIRR was 5.03 percent and, PI was 1.00. Thus the project was feasible. SVT result indicated that the project was risky; therefore had to be closely supervised, as the project was barely retainable to negative change.